Comparative analysis of post-focal filamentation of focused UV and IR laser pulses in air. (30th April 2015) - Geints, Yu E; Zemlyanov, A A; Ionin, A A; Mokrousova, D V; Seleznev, L V; Sinitsyn, D V; Sunchugasheva, E S
Abstract We report the results of laboratory experiments and numerical calculations of the spatial position and structure of a plasma channel produced in air by high-power focused femtosecond laser radiation with wavelengths of 740 and 248 nm as a result of its self-focusing and filamentation. A comparative analysis of the physical patterns of filamentation of IR and UV laser beams with variations in the beam focal length, transverse size and power is performed. It is found that a plasma channel beyond the linear focal waist of the laser beam is formed differently for two different spectral ranges.